2018
DOI: 10.1029/2018ja025643
|View full text |Cite
|
Sign up to set email alerts
|

High‐Frequency Thermal Fluctuations and Instabilities in the Radiation Belt Environment

Abstract: This paper overviews the electrostatic and electromagnetic theories of spontaneous emission in magnetized plasma as they relate to measured electric and magnetic field fluctuations in quiet time radiation belt and ring current region. The pervasively detected high-frequency fluctuations in the upper-hybrid frequency range as well as the background low-frequency range spectral profile in the whistler mode range are explained within the context of the spontaneous emission theory. The quasilinear calculation of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…In addition to the wave environment, we seek to understand the local plasma conditions (e.g., Thaller et al, ; Hwang & Yoon, , in this collection) that lead to the enhancement or suppression of these various wave modes and the consequences therein for the precipitation of the trapped populations. For instance, Greeley et al () in this collection have found that the plasmapause is likely a better indicator of microburst location than L‐shell.…”
Section: Particle Loss In the Inner And Outer Zonesmentioning
confidence: 99%
“…In addition to the wave environment, we seek to understand the local plasma conditions (e.g., Thaller et al, ; Hwang & Yoon, , in this collection) that lead to the enhancement or suppression of these various wave modes and the consequences therein for the precipitation of the trapped populations. For instance, Greeley et al () in this collection have found that the plasmapause is likely a better indicator of microburst location than L‐shell.…”
Section: Particle Loss In the Inner And Outer Zonesmentioning
confidence: 99%
“…First, we will consider the steady state wave equation in the presence of energetic electrons. The solution is essentially that which was already discussed in our previous papers (Hwang et al, ; Hwang & Yoon, ; Yoon et al, , ; Yoon, Hwang, et al, ), but herewith, we briefly include the essential analysis for the sake of completeness. We will then analyze the steady‐state particle equation in which the thermal noise fluctuation spectrum governs the velocity space diffusion.…”
Section: Dynamical Coupling Between Energetic Electrons and Upper‐hyb...mentioning
confidence: 99%
“…We have further employed this result in the thermal noise spectroscopy taking into account the antenna response function (Yoon, Hwang, et al, ) and successfully reanalyzed the VAP data. Finally, we have extended the basic methodology in order to include electromagnetic effects (Hwang & Yoon, ; Yoon et al, ) and showed that the electromagnetic effects have an appreciable impact on the low‐frequency portion of the fluctuation spectrum.…”
Section: Dynamical Coupling Between Energetic Electrons and Upper‐hyb...mentioning
confidence: 99%
See 1 more Smart Citation